(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This paper investigates the improvement of cotton–polyester blended yarn production technology through a comprehensive mathematical and mechanical analysis of the spinning process. The influence of key technological parameters on yarn quality is quantitatively described using mathematical models, and optimal control strategies are proposed to enhance production performance. Furthermore, the study highlights the novelty, practical significance, and economic benefits of the proposed technology for the textile industry of Uzbekistan. The developed mathematical framework provides a scientific basis for optimizing production processes, improving yarn quality, reducing manufacturing costs, and facilitating the digitalization and automation of modern textile enterprises.